Kesan Penggunaan Modul Berasaskan Pentaksiran Formatif Kecerdasan Pelbagai Terhadap Pencapaian Topik Jirim, Kebimbangan Pentaksiran Dan Efikasi Kendiri Murid Tahun Lima - Ahmad, Norasyikin (2021)
This study is conducted to develop a Multiple Intelligence Approach Module (Modul PKP) and Multiple Intelligence Rubric (Rubrik KP) to be applied in teaching and learning of States Of Matter topic in year five. Modul PKP is built based on ASSURE Model, which involves six steps which are (i) Analyze Learners, (ii) State Objectives, (iii) Select Instructional Methods, Media and Materials, (iv) Utilize Media and Materials, (v) Require Learner Participation, and (vi) Evaluate and Revise Instruction. The development of Rubrik KP is based on recommendations by Moskal (2003) which includes five categories, which are (i) Writing Goals and Objectives, (ii) Developing Performance Assessments, (iii) Developing Scoring Rubrics, (iv) Administering Performance Assessments, and (v) Scoring, Interpreting, and Using Results. Futhermore, this study examines the effectiveness of using Modul PKP with Rubrik KP, and the using of Modul PKP without Rubrik KP on the achievement in State Of Matter, assessment anxiety, self-efficacy and their retention. The role of assesment anxiety as a mediating variable for the relationship between self-efficacy and achievement in State Of Matter was also tested. A pre-test quasi experimental design, post-test and delayed post-test were used in this research. A total of 37 students in the first experimental group (E1) used Modul PKP with Rubrik KP, while a total of 34 students in the second experimental group (E2) used Modul PKP without Rubrik KP.